Leadership Succession and the Resilience of Electoral Authoritarian Regimes. (August 2020) - Zeng, Qingjie
How does leadership succession influence the dynamics of electoral competition in authoritarian regimes? Previous studies suggest that leadership successions tend to result in more competitive elections, creating favorable conditions for political changes. The literature, however, has not examined how the electoral impact of succession depends on specific mechanisms of succession management. We argue that the outgoing leader's clear designation of a successor plays an important role in neutralizing the electoral impact of succession. Clear designation, defined as the appointment of a "second-in-command, " prevents unbridled power struggle among ruling elites and grooms the successor for the leadership role. We support this argument by analyzing an original dataset covering over 400 elections in 60 authoritarian regimes. This article adds to the burgeoning literature regarding the effects of elections and institution-building on authoritarian resilience.